SAT0054 Favorable Long-Term Outcome of Early Inflammatory Arthritis in Clinical Practice: High Baseline Haq and Das28 at 3 Months Predict Use of Biologics. (15th July 2016) - Fanouriakis, A.; Papalopoulos, I.; Gergianaki, E.; Spyrou, G.; Rapsomaniki, P.; Terizaki, M.; Avgoustidis, N.; Repa, A.; Boumpas, D.T.; Sidiropoulos, P.
Abstract : Background: The course and natural history of early inflammatory arthritis (EA) varies widely and partly depends on the level of disease control in the early stages. Dedicated EA clinics follow a systematic targeted approach to improve long-term outcome of patients. Objectives: To assess the long-term outcome of EA following care in a dedicated early arthritis outpatient clinic. Methods: The "Early Arthritis (EA) Cohort" of the Department of Rheumatology of the University Hospital of Crete is a prospective cohort, which follows patients with inflammatory arthritis [RA, spondylarthritis or undifferentiated (UA)] of less than 6 months duration. Patients are followed quarterly for 2 years with systematic documentation of disease activity and function (measured by the DAS28 and HAQ, respectively), as well as for changes in therapy based on physician judgment. For the purpose of this study, we assessed long-term outcome (disease activity and function at 2 years) and examined prognostic factors for subsequent initiation of biologic agent. Results: Out of 559 patients referred to the EA Clinic, a total of 317 had a final diagnosis of RA or UA and were included in the present analysis [83.0% women, mean (SD) age at disease diagnosis 53.7 (15.1) years, 28.5% positive for RF or/and ACPA, mean (SD) number of tender and swollen joints at baseline 6.9 (6.0) and 5.5 (5.5), respectively. Mean (SD) DAS 28 at baseline was 4.59 (1.38) and mean HAQ was 0.59 (0.51), with 33.9% of patients having high disease activity (DAS28>5.1) and 18.3% reporting a HAQ≥1. At 2 years of follow-up, mean (SD) DAS28 and HAQ were 3.63 (1.3) and 0.49 (0.48), respectively (p<0.001 compared to baseline values for both). Nevertheless, 38.3% of patients still had moderate and 13.8% high disease activity at 2 years, while 19.3% reported a HAQ>0.75. During the course of follow-up, 34 patients received a biologic agent due to persistent high disease activity. In multivariate regression analysis, factors associated with initiation of biologic were HAQ at baseline [adjusted RR (95% CI) 4.91 (3.54–6.81)] and DAS28 at 3 months [adjusted RR (95% CI) 1.49 (1.15–1.93)]. Conclusions: Routine care with regular, objective documentation of disease activity and function is associated with satisfactory long-term outcomes in early inflammatory arthritis. Baseline impaired function and persistent disease activity at 3 months predict need for biologic treatment during follow-up. Disclosure of Interest: None declared